Radical Scavenging Activity and Quercetin Content of Muntingia calabura L. Leaves Extracted by Various Ethanol Concentration - Ratih Dyah Pertiwi; Suwaldi; Ronny Martien; Erna Prawita Setyowati (Journal of Food and Pharmaceutical Sciences, 2020)
Muntingia calabura is broadly cultivated and has become a common roadside tree in Indonesia that is known as "Kersen," or cherry. The current study aimed to determine the activities of the phytochemical constituent (i.e., phenolic and flavonoid total contents) with various concentrations of ethanolic extract of M. calabura leaves (EEMC) to determine the best one and the in vitro antioxidant activities and quercetin content using TLC Densitometry. The extraction was carried out by maceration with various concentrations of ethanol (96% v/v; 70% v/v and 50% v/v) to obtain the ethanolic extract of Muntingia calabura, L leaves. The determination of Quercetin was conducted by Thin Layer Chromatography (TLC) densitometry, and the total phenolic was analyzed with reagent Folin-Ciocalteu while the flavonoid content we identified by applying the colorimetric method. The antioxidant capacity was measured using the radical scavenging assay of 1,2-diphenyl-2-picrylhydrazyl (DPPH). The phytochemical study showed that phenolics, saponins, tannins, and flavonoids were present in all EEMC. The extract obtained by 96% ethanol showed the highest total antioxidant activity, reducing power and DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging activity. The same extract also exhibited the highest flavonoid content. However, the extract obtained by 70% ethanol showed the phenolic content, and the highest quercetin content was obtained by using 50% ethanol. The result from the EEMC analysis indicated that Muntingia calabura leaf extract contains essential bioactive compounds and shows potential as a source of antioxidants in M. calabura which uses 96% ethanol solvent and has the highest quercetin content in M calabura using 50% ethanol solvent.